RESISTING NON-EXISTENCE. MILJENKO JERGOVIĆ’S RUTA TENNENBAUM AS A POSTTRAUMATIC NARRATIVE - Sewior, Kinga (Porównania, 2013)
The subject of the article is the Croatian posttraumatic condition considered in the context of the establishments of modern research and the concepts of Holocaust Studies (M. Hirsch, S. Felman) and Memory Studies (A. Assmann). Local reception of the Holocaust in the recent social-cultural discourse is collated here with the memory of the fascist Independent State of Croatia (1941–1945) and the memory of the last Balkan War (1991–1995). Local historical context determines the uniqueness of Croatian experiences and conditions its asymmetric character which oscillates between hangman and victim positions; usually based on concealments and misrepresentations. The aforementioned assumption entails further targets: the analysis and interpretation of M. Jergović’s Ruta Tannenbaum which is considered here as the founding text to the examination discussion of the Croatian Past and, at the same time, as a postmemory text which uses narrative strategies specific for second and third generations of witnesses.